A Service Quality Assessment Tool for the Quick Service Restaurant Industry in Indonesia - Aprylia, Regyta; Santoso, Adi; Widhianingrum, Wahna (Almana : Jurnal Manajemen dan Bisnis, 2023)
The development of the fast-food restaurant industry, especially in the field of fast food throughout the world, is growing even in Indonesia. This study aims to analyze the factors that can affect consumer satisfaction in fast food restaurants in Indonesia through service quality, physical environment quality, and food quality. The population of this study is all consumers of McD fast food restaurants in Indonesia. The number of samples used in this study was 300 samples, where the number was obtained using the ISAC table. The data collection method uses online questionnaires using Google Forms. Data measurement uses a Likert scale. The data that has been collected is then entered into the AMOS 24 Software using the Structural Equation Modeling (SEM) analysis method to be used later to test the measurement model and the research hypothesis. The results of this study found that only service quality and food quality affected consumer satisfaction, while the quality of the physical environment did not affect McD's customer satisfaction.